Some development orientations of science, technology and innovation in Vietnam’s socio-economic development phase 2021-2030 - Minh, Hoang; Anh, Nguyen Lan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
The development of Science, Technology and Innovation (STI) in Vietnam has always been interested and focused by the Party and the State, has been confirmed in many important documents such as the National Development Platform, the acts, resolutions of the Party,... Over the past years, the Party's lines and policies have oriented the development of the science and technology industry and through which STI have achieved remarkable achievements, contributing to the national socio-economic development. However, compared to the social expectation as well as the important mission of STI, Vietnam's STI has not really become a driving force to improve labor productivity, enhance competitiveness, and promote development of socio-economic. The article summarizes the major guidelines and orientations of the Party and State on the development of STI, it presents an overview of the contributions of STI to socio-economic development in our country in the past, then it introduces an overview of the domestic and international context affecting the development of STI in the future and introducing the contents of STI presented in the draft 10-year socio-economic development strategy for the period of 2021-2030 to submit to the 13th National Party Congress. Code: <span style="text-align: left; color: #000000; text-transform: none; text-indent: 0px; letter-spacing: normal; font-size: 14px; font-variant: normal; font-weight: 400; text-decoration: none; word-spacing: 0px; white-space: normal; orphans: 2; -webkit-text-stroke-width: 0px; background-color: #ffffff;">20101101